HIV/AIDS policy guidelines for the Caribbean tourism sector (Quality Tourism for the Caribbean Port of SpainTT, 2001)
Seeks to assist hoteliers and restaurateurs in protecting their employees and guests, and in so doing protect the viability of their business.
Keywords: HIV